Superfractality of the set of numbers having no frequency ofn-adic digits, and fractal probability distributions - Pratsiovytyi, M. V.; Torbin, H. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the fractal properties (we find the Hausdorff-Bezikovich dimension and Hausdorff measure) of the spectrum of a random variable with independentn-adic (n≥2,n ∃N digits, the infinite set of which is fixed. We prove that the set of numbers of the segment [0, 1] that have no frequency of at least onen-adic digit is superfractal.